Hepatic metastasis from intracranial meningioma. Issue 737 (March 1987) - Jenkinson, M. L.; Watson, A. J.; Boyle, S.
Abstract : A 38 year old man presented with a hepatic mass which biopsy showed to be a metastasis from an intracranial meningioma. The meningioma originally followed cranial radiotherapy. Previous reports of extracranial metastases are reviewed.